Otomasi Pembayaran Siswa API Notifikasi pada Sekolah SMP Imtaq Darurrahim - Kholili, Akbar; Said, Fadillah (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2025)
The student payment process at SMP Imtaq Darurrahim still employs manual methods that cause transaction recording delays and lack of automatic notification systems. The research aims to design and develop a web-based student payment information system integrated with WhatsApp API to enable parents to receive real-time payment and outstanding fee information. The methodology employs the System Development Life Cycle (SDLC) waterfall model through requirement analysis, design, implementation, and testing phases. Research instruments include PHP, MySQL, and WhatsApp API integration for notifications. Results demonstrate that the system successfully records payment transactions accurately, generates monthly financial reports, and automatically sends notifications to parents. System implementation proves to enhance efficiency and accuracy in payment processes while strengthening communication between schools and parents.